Peran UPTD Perlindungan Perempuan Dan Anak Dalam Memberikan Perlindungan Hukum Terhadap Perempuan Korban Kekerasan Dalam Rumah Tangga - murniati, riska; Anderson, Irzal; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2023)
This study intends to examine how the UPTD for the Protection of Women and Children helps victims of domestic violence in Jambi City to obtain legal protection. A qualitative research methodology was used. Through the use of primary and secondary data, this research is descriptive in nature. Interviews and documentation are used as primary data collection methods, then the data will be analyzed qualitatively. The findings of this study indicate that the role of the UPTD for the Protection of Women and Children in providing legal protection for women victims of domestic violence has been going well, but not yet optimal. This is because there has been an increase in violence against women, and there will be a decrease in case data in 2022 because victims will tend not to report their experiences. In addition to providing legal protection for women victims of domestic violence, the UPTD for the Protection of Women and Children also functions as a mediator between victims and perpetrators. The task of the UPTD for the Protection of Women and Children is reduced to being a companion if the legal and religious courts are successful. In order to provide legal protection for women victims of domestic violence, the UPTD for the Protection of Women and Children must overcome challenges from victims, families of victims or perpetrators, and society. Based on this, the UPTD for the Protection of Women and Children seeks to provide this legal protection, in particular by conducting socialization and collaborating with related social organizations.